Pharmacokinetic Comparison of Isoalantolactone and Alantolactone in Rats after Administration Separately by Optimization of an UPLC-MS2 Method - Renjie Xu; Mengyue Wang; Ying Peng; Xiaobo Li (Journal of Chemistry)
Isoalantolactone and alantolactone are two major active ingredients that are present in many medicinal plants. In this study, a sensitive and rapid ultraperformance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method was developed for determination of the two compounds in rat plasma, separately. In this method, an electrospray ionization source was applied and operated in positive ion mode; multiple reaction monitoring (MRM) was selected for quantification using target fragment ions 233.2→187.1 for isoalantolactone (alantolactone) and 245.1→189.1 for internal standard (IS). Retention time of the lactones and IS was within 3.0 min. Further calibration suggested a linear regression can be calculated within 2.5–500 ng/mL for isoalantolactone and 4–500 ng/mL for alantolactone. This method was used to compare the pharmacokinetic characteristics of isoalantolactone and alantolactone at a single dose of 5 mg/kg into male Sprague-Dawley rats by intravenous administration separately. The levels of t1/2, Kel, CL, Cmax, and AUC were significantly increased in the alantolactone group compared to isoalantolactone. These results suggested that isoalantolactone was distributed and eliminated more rapidly than alantolactone in rats when administered, respectively.